1981
DOI: 10.3109/01485018108999297
|View full text |Cite
|
Sign up to set email alerts
|

Role of FSH in the Control of Testicular Function

Abstract: Follicle stimulating hormone (FSH) binds to the plasma membranes of Sertoli cells and, apparently, spermatogonia; the hormone may then be taken into the cytoplasm of its target cells and metabolized there. In the immature testis, binding of FSH to Sertoli cells leads to activation of adenylate cyclase, formation of cyclic AMP (CAMP), and activation of a CAMP-dependent protein kinase. There is a subsequent increase in the rates of RNA, protein, and DNA synthesis. Normal adult testis is unresponsive to FSH, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Sertoli cells are known to be responsible for nurturing the developing spermatids and on Leydig cells to produce androgenic hormones which enhance male reproductive traits. The results herein further confirmed the report of Davies (1981) that the administration of gonadotrophin to immature rats and mice increases the number of spermatogonia by reducing the proportion that degenerate. This may be due to a stimulatory effect of the hormone on DNA synthesis of the sperm cells.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Sertoli cells are known to be responsible for nurturing the developing spermatids and on Leydig cells to produce androgenic hormones which enhance male reproductive traits. The results herein further confirmed the report of Davies (1981) that the administration of gonadotrophin to immature rats and mice increases the number of spermatogonia by reducing the proportion that degenerate. This may be due to a stimulatory effect of the hormone on DNA synthesis of the sperm cells.…”
Section: Resultssupporting
confidence: 80%
“…This may be due to a stimulatory effect of the hormone on DNA synthesis of the sperm cells. Furthermore, gonadotrophin also increases the proportion of cells passing through meiosis and spermatogenesis (Davies, 1981;Haywood et al, 2003;Matthiesson et al, 2006) Means bearing different letters of superscript within the same row differ significantly (P<0.05). Orgebin-Crist (1968).…”
Section: Resultsmentioning
confidence: 99%
“…Early primary spermatocytes move across the barrier, and further germ cell development occurs in the adluminal compartment where Sertoli cells control the composition of the fluid which surrounds the germ cells by secret ing pyruvate and lactate which may support the synthetic activities and survival of germ cells, and they concluded that there is a close functional relationship between Sertoli cells and germ cells [21,22], Rivarola et al [23] proposed that Sertoli cells stimulate the syn thesis of RNA and DNA in spermatogenic cells. The Lcydig cell function may also be modified by Sertoli cells [25]. These observa tions and an already reported [9] decrease in the testosterone level in vitamin-D-deficient rats support our observation of decreased Leydig cell count of the present study.…”
Section: Discussionsupporting
confidence: 82%
“…The role of Sertoli cells and Leydig cells on the maturation of spermatozoa is known [13][14][15][16]. The Sertoli cells modify the Leydig cell function as well [17], The reversed GTP activity which is a marker of Sertoli cell func tion and return of the number of Leydig cells towards normal (table 1) may be responsible for the increased spermatogenesis seen in this study at lower doses of vitamin D administra tion.…”
Section: Discussionmentioning
confidence: 65%